Root proliferation and microbial enzyme strategies shape elevated CO₂ effects on wheat rhizosphere priming in farming soils - Jian Jin; Rachel Davis; Jennifer L. Wood; Gary J. Clark; Malcolm McCaskill; Yolanda Plowman; Ashley E. Franks; Caixian Tang (Plant and Soil, 2026)
Aims Elevated atmospheric CO 2 can impact soil organic carbon (SOC) cycling through increased photosynthetic carbon allocation in the rhizosphere, accelerating the decomposition of SOC (rhizosphere priming). How elevated CO 2 modifies priming intensity in different soil types and the associated microbial functional pathways remains poorly understood. Methods Using dual 13 C/ 15 N labelling, this study compared rhizosphere priming in wheat grown under ambient (400 ppm) and elevated (800 ppm) CO 2 in three soils widely used for crop production in southern Australia. Results Elevated CO 2 increased primed C by 28%, 23%, and 20% in Vertosol, Calcarosol and Chromosol, respectively at the booting stage ( p < 0.05). Elevated CO 2 enhanced root biomass, root length, and root‑derived CO 2 ‑C across soils; however, primed C expressed per unit root length remained unchanged, indicating that enhanced priming was associated with increased root proliferation rather than increased priming intensity per root unit. Elevated CO 2 did not affect plant N uptake and the relative contributions of fertilizer‑ and soil‑derived N, or N‑acquiring enzyme activities. However, it increased the activities of selected C‑acquiring and oxidative enzymes, with associations between enzyme functional groups and primed C in soils. Partial least squares path modelling showed that rhizosphere priming in the Vertosol was positively associated with oxidative enzyme activity, whereas the priming in the Calcarosol and Chromosol was associated primarily with C‑acquiring enzymes. Conclusions Elevated CO 2 enhances rhizosphere priming primarily through increased root‑derived carbon inputs and soil‑specific enzyme associations, rather than through enhanced N acquisition, under N‑amended cropping conditions.